Life on the Rocks: First Insights Into the Microbiota of the Threatened Aquatic Rheophyte Hanseniella heterophylla - Purahong, Witoon; Hossen, Shakhawat; Nawaz, Ali; Sadubsarn, Dolaya; Tanunchai, Benjawan; Dommert, Sven; Noll, Matthias; Ampornpan, La-aw; Werukamkul, Petcharat; Wubet, Tesfaye (Frontiers in Plant Science, 2021)
Little is known about microbial communities of aquatic plants despite their crucial ecosystem function in aquatic ecosystems. Here, we analyzed the microbiota of an aquatic rheophyte Hanseniella heterophylla growing at three areas differing in their degree of anthropogenic disturbance in Thailand employing metabarcoding approach. Our results show that diverse taxonomic and functional groups of microbes colonize H. heterophylla. Proteobacteria, Actinobacteria, Dothideomycetes, and Sordariomycetes form the backbone of the microbiota. Surprisingly, the beneficial microbes reported from plant microbiomes in terrestrial habitats, such as N fixing bacteria and ectomycorrhizal fungi were also frequently detected. We showed that biofilms for attachment of H. heterophylla plants to rocks may associate with diverse cyanobacteria (distributed in eight families, including Chroococcidiopsaceae, Coleofasciculaceae, Leptolyngbyaceae, Microcystaceae, Nostocaceae, Phormidiaceae, Synechococcaceae and Xenococcaceae) and other rock biofilm forming bacteria (mainly Acinetobacter, Pseudomonas and Flavobacterium). We found distinct community compositions of both bacteria and fungi at high and low anthropogenic disturbance levels regardless of the study areas. In the highly disturbed area, we found strong enrichment of Gammaproteobacteria and Tremellomycetes coupled with significant decline of total bacterial OTU richness. Bacterium involved with Sulfamethoxazole (antibiotic) degradation and human pathogenic fungi (Candida, Cryptococcus, Trichosporon, Rhodotorula) were exclusively detected as indicator microorganisms in H. heterophylla microbiota growing in highly disturbed area, which can pose a major threat to human health. We conclude that aquatic plant microbiota are sensitive to anthropogenic disturbance. Our results also unravel the potential use of these plants as biological indicators in remediation or treatment of such disturbed ecosystems.